Answer:
Ca^2+(aq) + SO4^2-(aq) → CaSO4(s)
Step-by-step explanation:
Step 1: The unbalanced equation
CaCl2(aq) + Na2SO4 (aq) → ...
Step 2: Balancing the equation
CaCl2(aq) + Na2SO4 (aq) → CaSO4 + NaCl
On the left side we have 2 times Cl (in CaCl2), On the right side we have 1 time Cl (in NaCl)
On the left side we have 2 times Na (in Na2SO4), on the right side we have 1 time Na (in NaCl)
To balanced the amount of Na and Cl we have to multiply NaCl, on the right side, by 2. Now the equation is balanced.
CaCl2(aq) + Na2SO4 (aq) → CaSO4(s) + 2NaCl(aq)
The net ionic equation, for which spectator ions are omitted - remember that spectator ions are those ions located on both sides of the equation - will look like this
Ca^2+(aq) + SO4^2-(aq) → CaSO4(s)